Frequency of Catheter Infections in Patients of Hemodialysis Despite Using Antibiotic Lock: Catheter Infections Despite Using Antibiotic Lock - Rashid, Sidra; Quershi, Maria; Moon, Farya; Qamar, Mehwish; Danial, Khurram; Abid, khadijah (Pakistan Journal of Health Sciences, 2022)
Non-tunneled catheters are associated with many complications, including infections and thrombosis. Objective: To determine the frequency of catheter infections in patients of hemodialysis despite using antibiotic locks, in a Tertiary Care Hospital Karachi. Methods: It was a cross-sectional study conducted at the department of nephrology, Liaquat national hospital and medical college, Karachi, Pakistan from 18th October 2020 to 18th April 2021. Patients of age 20 to 70 years of either gender on hemodialysis through double lumen catheter– non-cuffed for > 2 weeks were included in the study. Brief history was taken from all the patients. Gentamicin lock solutions were administered in all patients. Catheter tip was sent to institutional laboratory for culture and sensitivity to reach the outcome i-e catheter related infection. Results: The mean age was 58.97 + 14.82 years. The catheter related blood stream infection was in 21 patients (17.5%). The most common organism was coagulase negative Staphylococci (CoNS) (5.9%), followed by Vancomycin-resistant Enterococcus (VRE) (4.2%), respectively. There was insignificant association observed between catheter related blood stream infection and age groups, gender, comorbids, duration of catheter insertion and hemodialysis, site of catheter infection and reasons of hemodialysis (p > 0.05). Conclusions: Catheter-related infections in patients of hemodialysis despite using antibiotic locks is frequent but it has been observed that gram negative infections have responded well to gentamicin lock solution, where as in our study most common organism responsible for infection is coagulase negative Staph. followed by VRE